Little Global Nomads: Preparing Expatriate Children to Become Citizens of The World - Esamada Rose Nursaputri; Luh Putu Artini (Aulad: Journal on Early Childhood, 2026)
There is still limited research on how early expatriate childhood experiences shape Third Culture Kids (TCKs) into future global citizens. Global citizens are individuals who demonstrate intellectual growth, openness, tolerance, respect, and responsibility toward themselves, others, and the environment. Therefore, this study aims to review existing literature to understand how TCKs can be effectively prepared to become global citizens. This study is a qualitative study that employed a literature review approach on how expatriate children who experience social, cultural, and linguistic transition are prepared to be citizens of the world. The analysis was organized into three key concepts: the role of the family, the role of schools, and the role of the environment. Findings underline that these three elements influence expatriate children's ability to adapt, develop intercultural competence, and internalize global citizenship values. Altogether, they form an interconnected support system that supports resilience, cultural understanding, and global awareness in expat children as they navigate diverse contexts.